Railway Traffic Management as a Function of the New Infrastructure Manager - Mlakar, Damjan; Sever, Drago (Promet - Traffic&Transportation, 2007)
This article offers a survey of the cun·ent decentralised formof railway traffic management within the public railway infrastntcturein the The Republic of Slovenia, which is the result ofout-of-date and worn-out safety installations of railway stationsand railway lines. The article presents a new model of railwaytraffic management as the basis for efficient activity andharmonization of railway traffic management in the TheRepublicof Slovenia to the systems of railway traffic managementwithin EU. This article presents the advantages of a centralisedsystem of railway traffic management and demonstrates thatthe application of this system can solve the problem of decentralizedtraffic management as a function of the new infrastrncturemanager.